Financial Department, Worn Services / Hafizah Zainal Abidin - Zainal Abidin, Hafizah (University Technology MARA Sarawak, 2017)
Kitchen Industry or also known as Worx Services and Kitchen Plan is a private company established in the year 2012 where the company focus on architectural services and interior designing with a humble passion to serve various F&B owners and home residents from all walks of life with quality and reasonably priced commercial kitchen equipment. Previously, Kitchen industry known as Worxserv (M) Sdn. Bhd and in 4 June 2010, Worxserv (M) Sdn. Bhd has changed its name to KitchenPlan Sdn. Bhd which is still use until now and it became a company limited by shares.